Characterization of lumbar angle, pelvic sagittal balance and flexibility in preschoolers - Beresoski, Camila Mayumi; Camargo, Mariana Zingari; Siqueira, Cláudia Patrícia Cardoso M.; Vieira, Débora Beckner de Almeida Leitão Prado; Cibinello, Fabíola Unbehaun; Andraus, Rodrigo Antonio Carvalho; Fujisawa, Dirce Shizuko (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: The alignment between anterior superior and inferior posterior iliac spine is related to the lumbar curvature in the sagittal plane. Objective: To characterize the flexibility and angulations of the lumbar spine and the relation with the pelvic tilt in sagittal plane of preschool children. Methods: Participated in the study 138 children with ages ranging from five to six years and enrolled in eight public schools. The evaluation was performed by photogrammetry, pelvic sagittal balance test and limb stretching by fleximeter and Thomas test. Results: There was no difference in the lumbar angle with relation to gender, body mass and age. With regard to pelvic sagittal balance, the majority of preschoolers presented pelvic retroversion (56.6%). Children with pelvic anteversion (4.3%) presented a lower lumbar angle, indicating hyperlordosis. Children with pelvic sagittal balance presented better flexibility of the hamstring muscles than those with the pelvis in retroversion and anteversion. Conclusion: Flexibility was greatest in girls and in five-year-old children. The angle of the lumbar was 24.07°. The pelvis was retroversed in most children, differing from expected for the age group. The lowest angle of the lumbar region corresponded to a pelvis in anteroversion and balanced.